Laser-PSD based dynamic deflection monitoring of small- and medium-span beam bridges - Chen Xiong; Yingxiu Chen; Chengyu Cen; Yanmei Liang; Liu Mei; Qiling Luo; Wujian Long (Engineering Structures, 2026)

Effects of protein-bound iron supplementation on reproductive performance of sows and growth performance of piglets - Hongxuan Ye; Junyi Wu; Xuexun Feng; Qiling Chen; Zihao Huang; Bin Su; Songfeng Yang; Lili Wang; Hefeng Luo; Chengquan Tan (Domestic Animal Endocrinology, 2026)

Predictive biomarkers for valproic acid-induced hepatotoxicity in Chinese patients with epilepsy: the role of metabolites and genetic polymorphisms - Dingsheng Wen; Zhuojia Chen; Ziyi Chen; Xue Bai; Hongliang Li; Juan Chen; Qiling Dai; Guoping Zhong; Jiaming Qin; Guanzhong Ni; Min Huang; Liemin Zhou; et al. (Food and Chemical Toxicology, 2025)

Curcumin mitigates heat stress-induced gonadal dysfunction in roosters: insights from semen, histology, and transcriptome analysis - Qiling Su; Kai Kang; Huimingda Bao; Haien Chen; Jie Chen; Jiang Wu (Tropical Animal Health and Production, 2025)

The carbon footprint and ecological costs of citrus production in China are going down - Jinye Li; Shanshan Liang; Xiaomin Liang; Xiaojuan Wang; Xinchen Bai; Yilin Chen; Kongjie Wu; Xiaoman Liu; Zhihao Dong; Qiling Tan; Xuecheng Sun; Chengxiao Hu; et al. (Journal of Cleaner Production, 2025)

Difference in soil microbial necromass carbon accumulation induced by three crops straw mulching for 4 years in a citrus orchard - Xiaomin Liang; Yilin Chen; Xiaojuan Wang; Qiling Tan; Songwei Wu; Chengxiao Hu (Biology and Fertility of Soils, 2024)

Morphological characterization and transcriptome analysis of opercular deformity in golden pompano (Trachinotus ovatus) - Yuwei Wu; Dihao Huang; Qian Ma; Liuyong Wang; Qiling Zhou; Chunli Ran; Gang Chen (Aquaculture, 2024)

Histological characterization and lncRNA-mRNA integrated profiling analysis of the scales in rainbow trout (Oncorhynchus mykiss) under salinity acclimation - QiLing Zhou; ChangGeng Yang; YiKe Ren; Qian Ma; YunSheng Yang; LiuYong Wang; Gang Chen (Aquaculture, 2024)

A mutant GH3 family β-glucosidase from Oenococcus oeni exhibits superior adaptation to wine stresses and potential for improving wine aroma and phenolic profiles - Yuzhu Zhao; Biying Zhang; Huawei Gu; Tongxin Xu; Qiling Chen; Jin Li; Penghui Zhou; Xueqiang Guan; Ling He; Yanying Liang; Kekun Zhang; Shuwen Liu; et al. (Food Microbiology, 2024)

Data driven multi-objective design for low-carbon self-compacting concrete considering durability - Boyuan Cheng; Liu Mei; Wu-Jian Long; Qiling Luo; Jinrui Zhang; Chen Xiong; Yuqing Shu; Zhangjian Li; Song Gao (Journal of Cleaner Production, 2024)

Regulatory mechanisms of the edible alga Ulva lactuca polysaccharide via modulation of gut microbiota in diabetic mice - Qiling Ruan; Yihan Chen; Jiahui Wen; Yinghui Qiu; Yajun Huang; Yi Zhang; Mohamed A. Farag; Chao Zhao (Food Chemistry, 2023)

Synoptic view of an unprecedented red Noctiluca scintillans bloom in the Beibu Gulf, China - Qiling Xie; Nanyang Yan; Xue Yang; Ruichao Gao; Xinlong Chen; Hongjing Wu; Jun Zhao (Science of The Total Environment, 2023)

Cloning and Expression Profiling of the Gene vasa during First Annual Gonadal Development of Cobia (Rachycentron canadum) - Qian Ma; Jiehua Kuang; Gang Chen; Jiandong Zhang; Jiansheng Huang; Feifan Mao; Qiling Zhou (Fishes, 2022)
The vasa gene is essential for germ cell development and gametogenesis both in vertebrates and in invertebrates. In the present study, vasa (Rcvasa) cDNA was cloned from cobia (Rachycentron canadum) using the RACE amplification method. We found that the full-length cDNA sequence of Rcvasa comprises 2571 bp, containing a 5′-UTR of 145 bp, a 3′-UTR of 341 bp, and an open reading frame (ORF) of 2085 bp, encoding a protein of 694 aa. The deduced amino acid sequence contains 8 conserved motifs of the DEAD-box protein family, 7 RGG repeats, and 10 RG repeats in the N-terminal region. Comparisons of the deduced amino acid sequence with those of other teleosts revealed the highest percentage identity (86.0%) with Seriola quinqueradiata. By using semiquantitative RT-PCR, Rcvasa appeared to be specifically expressed in the testis and ovary, among 13 tissues analyzed. In addition, annual changes in Rcvasa expression levels were examined in the gonads by quantitative real-time PCR (qRT-PCR). The expression of Rcvasa in the testis first increased significantly at 120 dph (stage II–III), then stabilized as the testis developed from 185 dph (stage III) to 360 dph (stage V). During the development of the ovary (stage I to II), the expression of Rcvasa first increased and reached the highest level at 210 dph (stage II), then decreased. Furthermore, the results of chromogenic in situ hybridization (CISH) revealed that Rcvasa mRNA was mainly expressed in germ cells and barely detected in somatic cells. In the testis, Rcvasa mRNA signal was concentrated in the periphery of spermatogonia, primary spermatocytes, and secondary spermatocytes and was significantly weaker in spermatids and spermatozoa. In the ovary, Rcvasa mRNA signal was uniformly distributed in the perinuclear cytoplasm and was intense in early primary oocytes (stage I and II). These findings could provide a reference for understanding the regulatory mechanisms of vasa expression during the development of germ cells in cobia.

Effects of soil amendments on soil fertility and fruit yield through alterations in soil carbon fractions - Xiaomin Liang; Qin Chen; Muhammad Shoaib Rana; Zhihao Dong; XiaoDong Liu; Chengxiao Hu; Qiling Tan; Xiaohu Zhao; Xuecheng Sun; Songwei Wu (Journal of Soils and Sediments, 2021)

Susceptibility of oriental fruit fly, Bactrocera dorsalis (Diptera: Tephritidae) pupae to entomopathogenic fungi - Desen Wang; Qiling Liang; Minzhong Chen; Hui Ye; Yonglin Liao; Junyi Yin; Lihua Lü; Yanyuan Lei; Dongzhang Cai; Waqar Jaleel; Yurong He (Applied Entomology and Zoology, 2021)

Anti-phytopathogen, multi-target acetylcholinesterase inhibitory and antioxidant activities of metabolites from endophytic Chaetomium globosum - Wei Li; Xueqiong Yang; Yabin Yang; Rongting Duang; Guangyi Chen; Xiaozhan Li; Qiling Li; Shaohuan Qin; Shuquan Li; Lixing Zhao; Zhongtao Ding (Natural Product Research, 2016)

A new polyoxygenated farnesylcyclohexenone from Fungus Penicillium sp. - Yabin Yang; Fangfang Yang; Lixing Zhao; Rongting Duang; Guangyi Chen; Xiaozhan Li; Qiling Li; Shaohuan Qin; Zhongtao Ding (Natural Product Research, 2016)

Suitable Depth of Epidural Puncture in Nulliparous Pregnant Woman - Yi Luo; Dandan Zhang; Jing Zheng; Qiling Yang; Xiaohu An; Yi Chen; Dasong Yu; Zeyong Yang (Cell Biochemistry and Biophysics, 2015)